Energy Bridge Builder: Finland – Namibia Cooperation in Energy Business - Manyando, Obyster (My University, 2016)
This study is a result of a project initiated by the author in response to a looming electric power crisis in Namibia. Namibia has traditionally imported over half (at times up to 60%) of the electricity consumed in the country from neighbouring countries through Southern African Power Pool agreements. However, the exporting countries are facing power shortages as local demand continues to grow. It is against this backdrop that Namibia has embarked on a mission to become self-sufficient in power production. The objective of the study is to promote business collaboration between energy companies and public sector in Finland and energy companies and public sector in Namibia. The objective is achieved by assessing the availability of renewable energy resources in Namibia, identifying major actors, investor networks, energy needs, and barriers to entry into the Namibian energy industry. The primary aim of the research is to build a networking platform for energy stakeholders from the two countries and ultimately create business relationships. As a result, the study proposes entry modes into Namibia for Finnish companies. The secondary aim is to promote education and research cooperation between the University of Vaasa and the Namibia University of Science and Technology. The empirical data was collected through a survey distributed to Namibian energy stakeholders. The study revealed that the country is rich in renewable energy resources and has an established government-supported energy market. The study concluded that there are numerous business opportunities for Finnish energy companies in Namibia, and the best entry strategy into this young market is through strategic partnerships with local companies. Moreover, Namibian companies and the public sector are willing and able to contribute financially and strategically to partnerships with Finnish companies.
Keywords: energy business; Finland-Namibia cooperation; strategic partnerships; renewable energy; electricity; fi=Tuotantotalous|en=Industrial Management|; fi=Master's Degree Programme in Industrial Management|